Pengaruh Lingkungan Kerja Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di DPRD Kabupaten Tangerang - Intan Nursabila; Slamet Riyanto; Muhammad Nur Ikhsan (Jurnal Ekonomi, Bisnis dan Humaniora (EKSISHUM), 2025)
Work environment, work motivation, and work discipline are important factors that influence employee performance. This study aims to analyze the influence of these three factors on employee performance in the Tangerang Regency Regional People's Representative Council (DPRD). Using a quantitative method with a saturated sampling approach, this study involved 55 employees aged 20-41 years as the population and sample. Data analysis included validity, reliability, classical assumptions, regression, hypothesis, and coefficient of determination tests. The results showed that these three factors had a positive and significant influence on employee performance, both partially and simultaneously. Partially, the work environment t-count 3.317 > t-table 2.007, work motivation tcount 3.012 > t-table 2.007, and work discipline t-count 9.174 > t-table 2.007 had a significant influence. Simultaneously, the three variables also had a positive and significant influence F-count 158.114 > F-table 2.783. The conclusion of this study is that the environment, motivation, and work discipline are important factors that can be the basis for formulating policies to improve employee performance.